The role of limnological variables and habitat complexity in impacted tropical streams as regulatory factors on the flagellate protozoa community - Camargo,Janielly Carvalho (2012)
OBJECTIVE: To contribute to the knowledge of patterns of spatial and seasonal distribution of composition and species richness of flagellate protozoa in tropical impacted streams and to identify which variables (physical and chemical or descriptor variables of habitat complexity) control these attributes in these environments. METHODS: Samplings were performed in 10 tropical streams (5 urban and 5 rural) in two periods (summer and winter). Limnological variables were determined on the field (except for the concentration of nutrients), the habitat macrostructure was visually estimated in situ, using a quadrat and the species identification was performed in vivo, under optical microscope. RESULTS: In total, 106 taxa were identified, the order Euglenida was that contributed most to the species richness, probably due to the high tolerance to environmental changes. Multivariate analyses (ANOSIM and MDS) evidenced significant spatial and seasonal differences both for composition and species richness. The Bioenv and Mantel Test indicated that the patterns of composition and richness were controlled by physical and chemical variables indicative of water quality (pH, electrical conductivity, and concentration of nutrients). However, the species richness was also influenced by the habitat structural complexity and by its stability, which can be disturbed by the rainfall regime. CONCLUSIONS: The results showed that flagellate protozoa are sensitive to environmental changes, and thus can be used as efficient bioindicators of water quality, as has already been done with other aquatic organisms. Moreover, human activities that cause changes in the channel morphology of lotic ecosystems may determine the occurrence of flagellate species, once the simplification of the habitat structure leads to the reduction of species in the environment.